On Certain Class of Analytic Functions Related to Cho-Kwon-Srivastava Operator. (26th October 2011) - Ghanim, F.; Darus, M.
Abstract : Motivated by a multiplier transformation and some subclasses of meromorphic functions which were defined by means of the Hadamard product of the Cho-Kwon-Srivastava operator, we define here a similar transformation by means of the Ghanim and Darus operator. A class related to this transformation will be introduced and the properties will be discussed.